Transformational leadership in Mozambican primary schools - Bazo, Manuel (2021)
This dissertation is divided into six chapters. The current chapter provides an introduction, which has given a brief overview of the study concentrating on the context of the study, looking into the Mozambican education system as well as on the problem statement and research questions. In Chapter 2, there is a discussion of theoretical background by reviewing the literature that guided the study, exploring the nature of transformational leadership, the focus of which is on six dimensions of school leaders’ transformational practices (vision and goals, culture, structure, intellectual stimulation, individualized support, and performance expectation) as well as on organisational learning, individual teacher learning, and changing teaching practices. In Chapter 3 the rationale, the aim of the study, the general expectations, the research questions after literature review, and the hypotheses of the study are presented. Chapter 4 deals with a variety of issues and options with regard to the research methodology used in the study. Chapter 5 concentrates on the results by discussing and analysing the findings. Finally, Chapter 6 summarises and discusses the conclusions from the results of the study and provides recommendations for future research on educational leadership practices, and educational policy. The purpose of this chapter was to describe the situation which led to the problem investigated by this research. The context of the study and the problem statement were given as well as an introduction of the research questions. Finally an outline of the content of the chapters in this dissertation was provided